The development of transnational business associations during the twentieth century. Issue 2 (17th February 2023) - Rollings, Neil
Abstract: This article outlines the development of international non-governmental organisations (INGOs), and especially those relating to business, over the twentieth century. Using a variety of constructed datasets and drawing on population ecology approaches to interest groups, it is shown how business associations were numerically dominant for much of the twentieth century despite being largely excluded from accounts of the development of INGOs over this period. Growth in all such organisations was particularly prevalent in the immediate aftermath of the Second World War, but transnational business associations grew most rapidly at this time. The trends indicate that both the environmental context and the different dynamics of particular associational sectors explain these developments and that further research is needed to pin down more precisely the different factors at work.